2017
DOI: 10.1038/srep46452
|View full text |Cite
|
Sign up to set email alerts
|

The effect of L-PRF membranes on bone healing in rabbit tibiae bone defects: micro-CT and biomarker results

Abstract: More insight into the biological fundamentals of leukocyte platelet-rich fibrin (L-PRF) guided healing is necessary to recommend its application, in particular in deficient bone sites that need to support implants. This study investigated the short-term bone healing effect of L-PRF treatment in cylindrical non-critical sized bone defects with 3 mm diameter and 6 mm depth in tibiae of 18 adult male New Zealand White rabbits. After a randomization process, 96 bone defects were prepared and half of them were fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 39 publications
2
22
0
1
Order By: Relevance
“…According to Wang and Tao, L-PRF had an effect on proliferation and differentiation of osteoblasts; this was shown histologically in the rat used in their study, this was significantly showed radiographically in our study. In contrast to our study Faot., et al (26) found that the L-PRF did not enhance bone tissue repair in rabbit tibia during 4 weeks experiment but our results are similar to Kim., et al (27) that they found that the addition of L-PRF, in the bone defect in the rabbit skull, increased the bone formation at the 6th week The positive results of PRF could be attributed to mitogenic response in the periosteum under the influence of growth factors released from the platelets entangled within fibrin matrix.…”
Section: Discussionsupporting
confidence: 86%
“…According to Wang and Tao, L-PRF had an effect on proliferation and differentiation of osteoblasts; this was shown histologically in the rat used in their study, this was significantly showed radiographically in our study. In contrast to our study Faot., et al (26) found that the L-PRF did not enhance bone tissue repair in rabbit tibia during 4 weeks experiment but our results are similar to Kim., et al (27) that they found that the addition of L-PRF, in the bone defect in the rabbit skull, increased the bone formation at the 6th week The positive results of PRF could be attributed to mitogenic response in the periosteum under the influence of growth factors released from the platelets entangled within fibrin matrix.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were observed in another study, where platelet-rich fibrin did not increase bone regeneration in non-critical size defects in rabbit tibia. The authors suggested that this may be partially due to difficulty in retention of PRF at the defect site because of the anatomy of the tibia [40]. The differences in the biology and physiology can also affect the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is difficult to correlate the findings obtained in the present study with those described in the literature. However, it should be noted that clinical and preclinical studies that assessed the effects of L‐PRF on bone regeneration show contradictory results (Oliveira et al, ; Potres et al, ; Lekovic et al, ; Tanaka et al, ; Faot et al, ; Jeong et al, ; Zhang et al, ). One of the explanations for these discrepancies could be related to the L‐PRF preparation protocol.…”
Section: Discussionmentioning
confidence: 99%